Performance Evaluation of Return, Risk and Liquidity of Firms Newly Listed in Tehran Stock Exchange - Mehrjardi, Mehdi Alikhani; Ghadamyari, Mohammad; Mahboobi, Yousef (International Journal of Economics and Financial Issues, 2017)
It is essential to understand the behavior of initial offerings in comparison with other firms in different periods of recession and prosperity of stock market, considering three indicators of performance, i.e. return, risk and liquidity. The focus of this study is performance evaluation of newly listed stocks considering above indicators in different periods of recession and prosperity. For this purpose, 317 active firms which were not consistently inactive for three months or traded by March 20, 2006 were studied. Based on the suggested model, performance of the newly listed stocks was evaluated simultaneously based on three indicators of performance. Then, performance of the newly listed stocks was evaluated individually based on those three indicators. Through MANOVA, performance of the newly listed stocks was evaluated better than other stocks. Keywords: initial public offering, return, risk, liquidity JEL Classifications: G11, G32